Contribuição à análise de lajes nervuradas em pavimentos de garagem - Tenório, Daniel Almeida (2011)
This work is turned to a structural element with a large number of scientific studies, waffle slab. The aim of this study was to elucidate two recommendations of the Brazilian codes that have different values of international codes. The first concerns the accidental loading to garage floor recommended by the Brazilian code, where there is not recommending the use of concentrated loads, the same being recommended by international codes. The second is related to the different recommendations between the Brazilian code and international codes regarding the calculation of the bending of the table of waffle slabs. To meet the objectives of this work, some numerical simulations of floors containing a single waffle slab, modeled as one-way waffle slab and two-way waffle slab, were made using the finite element method and grillage analysis using specific software. The focus of structural analysis turned to determining the maximum bending moments acting on the flange of waffle slabs and arrows. The answers to these simulations showed that for garage floors, it is important to consider concentrated loads (vehicles). As utilization in structural designs of concentrated loads is a process slow and complicated, were defined values of distributed loads to provide arrows and moments in the ribs equal to those generated by the concentrated loads. On the analysis of bending on the table of waffle slabs, some recommendations were found, some of these one being equal to the Brazilian code, and other to international codes and some different compared to all codes.